Self-perception of dizziness and the relationship with the easing of COVID-19 social distancing rules, immunization and vitamin supplementation - de Oliveira, Priscila Feliciano; Lima, Meline dos Santos; Santos, Emanuelle de Jesus; Santos, Tamara Figueiredo do Carmo; Cabral, Aline; Raposo, Oscar Felipe Falcão (Seven Editora, 2023)
Objective: To analyze the behavior of people with dizziness when faced with the easing of the COVID-19 social distancing rules, immunization and use of vitamin supplementation. Method: A self-perception questionnaire was applied in electronic format, during the period of easing of the COVID-19 social distancing rules, with 19 closed questions. The following aspects were addressed: identification, general health (COVID-19, influenza, immunization and comorbidities), time of onset of dizziness, means of protection against COVID-19, vitamin supplementation, homemade recipes and use of teas. Results: 667 Brazilians were interviewed, all eligible to participate in the research. Of these, 261 (39.1%) self-reported the presence of dizziness, with a mean age of 37.91 years, with a prevalence of females. The use of masks and hand hygiene were protective measures that continued to be adopted during the easing of the COVID-19 social distancing rules, with 89.2% reporting, even after having been immunized, that they were afraid of contracting SARS COV -two. It was observed that 11.1% triggered dizziness after a positive test for COVID-19; in addition, 32.2% consulted a nutritionist to start the supplementation process (p=0.005), 65.1% used vitamin supplements (p=0.001) and 19.8% reported having used homemade recipes such as Espinheira Santa Tea and Chamomile, Ginko Biloba in order to minimize dizziness. Conclusion: Participants with dizziness were diagnosed with a vestibular disorder by a specialist, since there was a positive relationship with dizziness in the post-COVID-19 period. In order to reduce vestibular symptoms, the interviewees consulted a nutritionist to start vitamin supplementation and used vitamin complexes from A to Z, among others such as zinc, vitamin B12 and homemade teas. Even after the COVID-19 immunization, the participants continued to follow the guidelines for hand hygiene and the use of protective masks. DOI:https://doi.org/10.56238/emerrelcovid19-034